Zebra Mussel Holobionts Fix and Recycle Nitrogen in Lagoon Sediments - Marzocchi, Ugo; Bonaglia, Stefano; Zaiko, Anastasija; Quero, Grazia M.; Vybernaite-Lubiene, Irma; Politi, Tobia; Samuiloviene, Aurelija; Zilius, Mindaugas; Bartoli, Marco; Cardini, Ulisse (Frontiers in Microbiology, 2021)
Bivalves are ubiquitous filter-feeders able to alter ecosystems functions. Their impact on nitrogen (N) cycling is commonly related to their filter-feeding activity, biodeposition, and excretion. A so far understudied impact is linked to the metabolism of the associated microbiome that together with the host constitute the mussel’s holobiont. Here we investigated how colonies of the invasive zebra mussel (Dreissena polymorpha) alter benthic N cycling in the shallow water sediment of the largest European lagoon (the Curonian Lagoon). A set of incubations was conducted to quantify the holobiont’s impact and to quantitatively compare it with the indirect influence of the mussel on sedimentary N transformations. Zebra mussels primarily enhanced the recycling of N to the water column by releasing mineralized algal biomass in the form of ammonium and by stimulating dissimilatory nitrate reduction to ammonium (DNRA). Notably, however, not only denitrification and DNRA, but also dinitrogen (N2) fixation was measured in association with the holobiont. The diazotrophic community of the holobiont diverged substantially from that of the water column, suggesting a unique niche for N2 fixation associated with the mussels. At the densities reported in the lagoon, mussel-associated N2 fixation may account for a substantial (and so far, overlooked) source of bioavailable N. Our findings contribute to improve our understanding on the ecosystem-level impact of zebra mussel, and potentially, of its ability to adapt to and colonize oligotrophic environments.